(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Background Hypertension is a major risk factor for strokes, cardiovascular and kidney diseases worldwide and it has considerable variation in its prevalence across different geographic locations and ethnic groups. Objectives This study aimed to estimate the prevalence of hypertension and to determine its major risk factors among women. Methods A Descriptive cross-sectional community based study was conducted in Tirira Madani village –Sennar state- Sudan. A total of 255 women aged (15 – 75) years were interviewed using a structured questionnaire. Blood pressure was measured twice. Hypertension was taken as blood pressure ≥ 140 mmHg and/or ≥ 90 mmHg for systole and diastole respectively. Descriptive cross-tabulations and bivariate analyses were used. The statistical significance was tested using chi-square test. Predictor factors to hypertension were tested by logistic regression. Results Prevalence of hypertension among participants was 25.9%. Factors found to be associated with hypertension were; age, illiteracy, low salt intake, family history of hypertension, Coffee intake of more than two cups daily, fish consumption, low physical activity, and high socio-economic status. Certain ethnic groups were at increased risk compared to others (RR=2.11, 95%CI: 1.265 – 4.588). Logistic regression model showed age, ethnicity, physical activity level, education level and family history were predictors of hypertension (P-value <0.05).Conclusion Hypertension was prevalent in rural Sudan. Age, ethnicity, socio-economic status, level of education and family history of hypertension were the major risk factors of hypertension.